Social Media Marketing, Brand Image, dan Brand Trust: Pengaruhnya Terhadap Purchase Intention Skincare Lokal - Jovanka Thessalonian; Wisnu Budi Prasetyo (Economic Reviews Journal, 2025)
This study aims to analyze the direct and indirect effects of Social Media Marketing, Brand Image, Brand Trust, and Purchase Intention in local skincare product purchases by Z generation in Jabodetabek. The research is motivated by the increasing role of social media as a marketing tool in the beauty industry, particularly within Indonesia’s skincare market. The focus of this study is on Z generation consumers, who are highly active on social media and rel yon it as a primary source of information before makin purchasing decisions. The results indicate that Social Media Marketing influences Purchase Intention both directly and indirectly (mediated by Brand Trust). Similarly, Brand Image affects Purchase Intention directly and indirectly (also mediated by Brand Trust). Brand Trust serves as the mediating variable in this study, both in mediating the relationship between Social Media Marketing and Purchase Intention and in mediating the relationship between Brand Image and Purchase Intention. Local skincare brands must prioritize creative and interactive Social Media Marketing strategies to enhance engagement and trust. Building a strong Brand Image on digital platform sis critical for maintaining credibility. Additionally, honesty in sales practices and transparent communication are essential to strengthen Brand Trust. This research underscores the importance of brands optimizing their Social Media Marketing, Brand Image, Brand Trust strategies to drive high consumer Purchase Intention for local skincare products.